Perhadliran dalam Sakramen Perjamuan Kudus di Gereja Protestan Maluku - Sharon Michelle O. Pattiasina (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2019)
The article aims to analyze the meaning of perhadliran in the Sacrament of Holy Communion in the Protestant Church of Maluku. This study using qualitative methods with the techniques used are interviews and literature studies. In the study, data was obtained that the Protestant Church of Maluku did not have a clear historical background regarding the use term of the perhadliran. However, perhadliran was carried out by the Protestant Church of Maluku with the aim of preparing themselves before the Holy Communion was held. The Protestant Church of Maluku interpreted the perhadliran as a process of self-prepation, but some interpreted it as a means of confession, it is required to answer the four questions of the perhadliran. Based on the research data above, it is found that the perhadliran has three meanings, namely the meaning of self-preparation, the meaning of recognition, and the meaning of the agreement.  Abstrak: Artikel ini bertujuan menganalisis makna perhadliran dalam sakra-men perjamuan kudus di Gereja Protestan Maluku (GPM). Penelitian ini menggunakan metode kualitatif dengan teknik yang dipakai ialah wawancara dan studi kepustakaan. Dalam penelitian, diperoleh data bahwa GPM tidak me-miliki latar belakang historis yang jelas terkait penggunaan istilah perhadliran. Namun, perhadliran dilakukan GPM dengan tujuan untuk persiapan diri sebe-lum Perjamuan Kudus dilaksanakan. GPM memaknai perhadliran sebagai proses persiapan diri, namun sebagian memaknai se-bagai sarana pengakuan dosa, karena di dalam ibadah perhadliran anggota jemaat diharuskan menjawab empat pertanyaan perhadliran. Berdasarkan data-data peneli-tian di atas maka ditemukan bahwa perhadliran memiliki tiga makna yaitu makna per-siapan diri, makna pengakuan dan makna perjanjian.